2008
DOI: 10.2105/ajph.2007.126441
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Educational Attainment on Depression and Risk of Type 2 Diabetes

Abstract: Objectives-We investigated the association between major depressive disorder and type 2 diabetes, whether that association is explained by health behaviors, and whether it is influenced by educational attainment.Methods-We used discrete-time Cox proportional hazards models to determine the risk of type 2 diabetes associated with depression in a 23-year population-based cohort study. Results-Major depressive disorder was associated with higher risk of type 2 diabetes (hazard ratio[HR]=1.62) after we controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 30 publications
4
48
1
1
Order By: Relevance
“…We also included a number of other variables so we could control for several known predictors of depression and anxiety. These included: years in education, as a longer period in education has been found to be related to 9 lower levels of depression in later life [35]; certain medications (antidepressants, anxiolytics, mood stabilisers/anti-epileptics, neuroleptics, sleeping tablets, betablockers and tetrabenazine, the latter of which can have side-effects of anxiety and depression [36]); past use of antidepressants and anxiolytics, and history of depression (no assessment of history of anxiety is included in REGISTRY); cigarette use (number per day) and alcohol use (units per day), as these have both been found to affect depression and anxiety [37][38][39]; largest CAG repeat length and the Total Motor Score from the UHDRS (a composite measure of different motor tasks, including oculomotor function, dysarthria, chorea, dystonia, gait and postural stability, with higher scores indicating more motor impairment).…”
Section: Datamentioning
confidence: 99%
“…We also included a number of other variables so we could control for several known predictors of depression and anxiety. These included: years in education, as a longer period in education has been found to be related to 9 lower levels of depression in later life [35]; certain medications (antidepressants, anxiolytics, mood stabilisers/anti-epileptics, neuroleptics, sleeping tablets, betablockers and tetrabenazine, the latter of which can have side-effects of anxiety and depression [36]); past use of antidepressants and anxiolytics, and history of depression (no assessment of history of anxiety is included in REGISTRY); cigarette use (number per day) and alcohol use (units per day), as these have both been found to affect depression and anxiety [37][38][39]; largest CAG repeat length and the Total Motor Score from the UHDRS (a composite measure of different motor tasks, including oculomotor function, dysarthria, chorea, dystonia, gait and postural stability, with higher scores indicating more motor impairment).…”
Section: Datamentioning
confidence: 99%
“…Many epidemiological, psychological and psychiatric studies aim to study causal environmental effects without being designed to do so. For example, studies have shown associations between 'exposures' such as education or life events and mental health outcomes (Bannink et al, 2013;Dalgard et al, 1995;Flouri & Kallis, 2011;Kinderman et al, 2013;Mezuk et al, 2008), and such associations often are interpreted as evidence of causal effects. However, as there are substantial genetic influences on both educational level and certain types of life events Kendler & Baker, 2007;Kendler et al, 1999;Tambs et al, 2012) the associations may be partly or entirely explained by genetic confounding.…”
Section: Introductionmentioning
confidence: 99%
“…Examining the papers cited in the reviews and others published since then, we noted that the more clinically robust the instrument used to classify the depression was, the more likely the study was to find a significant association between T2D and a previous diagnosis of depression (58,92) or depressive symptoms (28,32,43,79). The studies defining depression on the basis of depressive symptoms collected within a general mental health scale were less likely to find a statistically significant elevated risk (8,46), although some did (13,25).…”
Section: Mental Health and The Development Of Type 2 Diabetesmentioning
confidence: 95%
“…Two studies found an interaction with education (13,58), such that individuals with low education and depression were at greater risk for the development of T2D than both those with more education and depression and those with neither risk factor. Again, two studies also found gender differences, reporting an association of T2D with depression in males but not in females (25,92).…”
Section: Mental Health and The Development Of Type 2 Diabetesmentioning
confidence: 99%
See 1 more Smart Citation